GROWTH AND YIELD OF MUSTARD AS INFLUENCED BY NITROGEN LEVELS, ROW SPACING AND MOISTURE CONSERVATION PRACTICES IN RAINFED CONDITION ON ERODED SOIL OF CENTRAL U.P. - Sachan, S.S.; Singh, R.K; Koshta, S.K. (Journal of Soil and Water Conservation, 2022)
A field experiment was conducted at Kanpur during ’Rabi’ season of 1990-91 to find out the row spacing, moisture conservations, yield, total water van. Use (WU) and water use efficiency (WUE) of rainfall mustard var. Vaibhay. The result reveals that all the growth, yield attributes and yield were found maximum under a row spacing of 60 cm (45 cm) in case of yield), paddy straw mulch and 60 kg N has’. Grain yield increased by 1.36 and 2.39 q has’ over control with interlocutor and paddy straw mulch respectively and increases were found significant. Application of 20, 40 and 60 kg N ha.’ significantly increased the grain yield by 1.47,2.58 and 3.55 q hae’ over control. A row spacing of 45 cm decreased the WU and increased WUE over 60 cm. Paddy straw mulch decreased WU by 13 mm and increased WUE by 1.97 kg grain ha mm-’ over control. Maximum total WU and WUE were found under 60 kg N ha-’. Additional net return over control was also realised with paddy straw mulch (Rs. 1801) and 60 kg Naha.’ (Rs. 2911) with a row spacing of 45 cm (Rs.1135) over 60 cm.